Praktyczne aspekty wdrażania metody CFA na przykładzie starostwa powiatowego w Kamiennej Górze - Kachniarz, Marian (Practical Aspects of Implementing the CAF Method on the Example of Kamienna Góra District Office, 2008)
The article presents results of Common Assessment Framework in Kamienna Góra district office. It shows the procedure carried out between 2001 and 2007. On the basis of these practical experiences, the author formulates general conclusions concerning the CAF model in public administrations. In author's opinion, this model cannot be treated as an objective measure of potential of public administration units. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 305-313